Khepok Bites Enterprise / Nur Alia Nabila Musa... [et al.] - Musa, Nur Alia Nabila; Sheikh Muzib, Siti Kasmarissa; Mohd Fudzi, Siti Najiha; Hassan, Nur Atikah Izzati; Basir, Siti Nur Hartini (2019)
The name of our business 1s Khepok Bites. This business is being run by five members. It is a partnership business. Our pian is to become the ieading provider of ··keropok lekor" in Malaysia. The product of our business is keropok lekor which is a traditional food of Terengganu, Malaysia. Recently, people love to eat simple food but taste delicious. As the entrepreneurs, we think that keropok lekor is a simple and affordable dishes that can be dignify in this country. We take a step tmward in making a business in upgrading and enchancing the way keropok lekor served. Customers can choose their own favourite toppings and serving ways in eating keropok lekor.